Ocular Causes of Abnormal Head Position: Strabismus Clinic Data - Kadriye Erkan Turan; Hande Taylan Şekeroğlu; İrem Koç; Esra Vural; Jale Karakaya; Emin Cumhur Şener; Ali Şefik Sanaç (Türk Oftalmoloji Dergisi, 2017)
Objectives: To determine the most common ocular causes and types of abnormal head position (AHP) and describe their clinical features. Materials and Methods: Patients with AHP who had been followed in the strabismus unit were retrospectively reviewed. Demographic features and orthoptic characteristics were recorded. Results: A total of 163 patients including 61 women (37.4%) and 102 men (62.6%), with a mean age of 19.9±18.3 were recruited. The most common causes of AHP were determined as fourth cranial nerve palsy (33.7%), Duane retraction syndrome (21.5%), sixth cranial nerve palsy (11%), nystagmus blockage syndrome (9.8%) and Brown syndrome (6.7%). Other less frequent causes were A-V pattern strabismus, comitant strabismus, thyroid orbitopathy and third cranial nerve palsy. The most common types of AHP were head tilt (45.4%) and face turn (36.8%). Out of 142 patients whose visual acuity could be evaluated, 28.2% had amblyopia. The frequency of amblyopia varied depending on the diagnosis (p<0.001), while there was no relation between amblyopia and different types of AHP (p=0.497). Stereopsis and fusion could be tested in 128 patients and 43.8% of them had stereopsis and fusion. The presence of stereopsis and fusion was found to be related with the diagnosis (p=0.001), whereas it was not related with the types of AHP (p=0.580). The presence of amblyopia was not significantly associated with fusion (p=1.000) or stereopsis (p=0.602). Conclusion: There are many ocular pathologies that cause AHP. Patients with similar diagnoses may have different types of AHP. Patients may have amblyopia and impaired binocularity despite AHP. Therefore, all patients with AHP should be examined in detail and these points should be considered in the treatment plan.